OJO DE AGUA, ANOTHER WAY OF UNDERSTANDING LEARNING - Javier Herreros Gil; Jose Maria Sola Reche; Maria Angustias Hinojo Lucena (European Scientific Journal, ESJ, 2015)
Since the traditional school as we know it today was established as an educational system in most countries, there have always been alternatives to it, all of them with different approaches. In this article Ojo de Agua is analyzed, an educational space created in Orba (Alicante, Spain), where education is understood as a process of self-learning, which is the student himself who mark the rhythms and interests in guiding his own development.